1990
DOI: 10.1095/biolreprod43.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Major Phosphoinositide-specific Phospholipase C of Human Amnion

Abstract: Most of the phosphoinositide-specific phospholipase C activity in human amnion at term was found to be attributable to a single isoform (Mr 85,000). Phospholipase C purified from amnion catalyzed the calcium-dependent hydrolysis of both phosphatidylinositol and phosphatidylinositol 4,5-bisphosphate. The high phospholipase C activity of amnion cells isolated at 38-41 weeks of gestation declined greater than 80% during the initial 2-5 days of culture to values characteristic of amnion tissue in early gestation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…DiRenzo and colleagues 41 measured the specific activity of PLC in amnion and decidua obtained after elective caesarean section and spontaneous labor at term, and found no effect of labor on enzyme activity. Bala and associates 77 confirmed the observation that the concentration of PLC in term human amnion is characteristically high; however, they found that the increased levels of the enzyme were not maintained when amnion tissue or dispersed amnion cells were cultured for 2-10 days. The loss of PLC was selec tive, because it was not accompanied by losses in the activity of other enzymes of lipid metabolism such as PLA 2 and phosphatidylinositol synthase, and was not prevented by the inclusion of serum in the cul ture medium.…”
Section: Changes In Enzyme Levelsmentioning
confidence: 80%
See 3 more Smart Citations
“…DiRenzo and colleagues 41 measured the specific activity of PLC in amnion and decidua obtained after elective caesarean section and spontaneous labor at term, and found no effect of labor on enzyme activity. Bala and associates 77 confirmed the observation that the concentration of PLC in term human amnion is characteristically high; however, they found that the increased levels of the enzyme were not maintained when amnion tissue or dispersed amnion cells were cultured for 2-10 days. The loss of PLC was selec tive, because it was not accompanied by losses in the activity of other enzymes of lipid metabolism such as PLA 2 and phosphatidylinositol synthase, and was not prevented by the inclusion of serum in the cul ture medium.…”
Section: Changes In Enzyme Levelsmentioning
confidence: 80%
“…This suggests that PLC activation per se does not necessarily lead to increased PGE 2 output in amnion cells. Furthermore, Bala and coworkers 77 observed that the spontaneous loss of PLC activity did not diminish the PGE 2 response of cultured amnion cells to vasopressin. A possible interpreta tion of this result is that PLC-δ, the isoform appar ently expressed in the amnion at high levels, is not involved in the agonist-induced changes of ,PLC activity and PGE 2 synthesis.…”
Section: Regulation Of Enzyme Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…We have shown that replenishment of nutrients can activate PI-PLC over an extended period of time. We have used U-73122, a compound that has been extensively used in studying possible functions of PI-PLC in mammals (for example, Bala et al, 1990 [1] ; Bleasdale et al, 1990 [4] ; Hirose et al, 1999 [19] ; Powis et al, 1991 [41] ; Smith et al, 1990 b [50] ) and plants (Knight et al, 1997 [24] ; Koch et al, 1998 [25] ; Pingret et al, 1998 [40] ; StaxØn et al, 1999 [52] ). Its near-identical analogue U-73343 does not inhibit PI-PLC.…”
Section: Introductionmentioning
confidence: 99%